Painless chronic pancreatitis. Issue 11 (November 2020) - Amodio, Antonio; De Marchi, Giulia; de Pretis, Nicolò; Crinò, Stefano Francesco; D'Onofrio, Mirko; Gabbrielli, Armando; Ciccocioppo, Rachele; Frulloni, Luca
Abstract: Background: Painless chronic pancreatitis (CP) is a rare form of the disease. Aim: To evaluate the prevalence and the characteristics of this overlooked form of pancreatitis. Methods: Patients with a diagnosis of CP and absence of pain were selected, excluding patients suffering from autoimmune pancreatitis. Clinical data, imaging features, and exocrine and endocrine function were therefore analyzed. Results: Among 781 patients observed between 2010 and 2016, 74 patients with painless CP (9.5%) were selected. Mean age at diagnosis was 60.8 (SD 10.8) years. 38(51%) individuals did not report any symptom, 36(49%) were affected by symptoms other than pain. Pancreatic calcifications were diagnosed in 70 patients (95%), main pancreatic duct dilation in 55(74%), and pancreatic atrophy in 39(53%).Thirty-six patients (55%) had severe exocrine pancreatic insufficiency(EPI). Diabetes was observed in 34 out of 72 patients (47%). During a mean follow-up of 2.9 (SD 2.8) years, only a mild pancreatitis was diagnosed in a 71-year old female. No patient underwent endoscopic treatment or surgery, developed pancreatic cancer or died. Conclusions: In a tertiary center painless CP is observed in 10% of cases, and it is frequently associated with EPI. The probability of onset of pain is very low in a short-term follow-up.